Tinjauan Sistematis Perencanaan Pembangunan Desa di Indonesia: Tata Kelola, Partisipasi, dan Transformasi Digital - Ningsih, Yulia; Gungnaidi, Afril; Putera, Roni Ekha (Faculty of Social Science, Universitas Negeri Padang, 2024)
Village development is fundamental to improving community welfare and reducing regional disparities. This study analyzes village development planning in Indonesia using a systematic literature review approach on recent studies. The findings indicate that the effectiveness of village development planning is influenced by community participation, institutional capacity, and technological integration. However, community participation faces limited understanding and ineffective deliberation mechanisms. Weak institutional capacity at the village level also hinders the implementation of development programs, highlighting the need to strengthen governance systems and ensure transparency in village fund management. Moreover, the utilization of technology in village development planning remains suboptimal, despite its potential to enhance planning efficiency and program monitoring. This study emphasizes the importance of a holistic approach to village development planning by integrating social, economic, and technological aspects to create a more adaptive and sustainable development model. The findings contribute to policymakers in formulating more inclusive and locally driven village development strategies. Furthermore, this study serves as a reference for future research in developing a more responsive village development planning model that addresses social and economic challenges in Indonesia.